Perception of Nursing Students toward Academic Learning Environment in a College of Kathmandu - Koirala, Manisa; Koirala, Surya; Neupane, Sharmila (Journal of Institute of Medicine Nepal, 2019)
Introduction: A supportive and systematic design of academic learning environment has been important for transfer of learning in clinical context, can lead to positive outcomes for graduates and best prepares for professional life. The objective of this study was to find out the perception of nursing students toward academic learning environment. Methods: The descriptive, cross sectional study design was used among 172 proficiency certificate level (PCL) nursing students at Maharajgunj Nursing Campus, Kathmandu Nepal. The data were collected by using Dundee Ready Education Environment Measure (DREEM) Inventories with complete enumeration technique which was developed by Roff et al (1997). Data were analyzed using descriptive and inferential statistics. Results: Overall mean score of academic learning environment was found 142.78 out of 200 for 50 items which was in the ranged for ‘positive’ learning environments. The total mean score for perception of learning was 34.4 out of 48; for perception of teacher 30.7 out of 44; for academic self-perception 25 out of 32; for perception of atmosphere 33.3 out of 48; for social self-perceptions 19.3 out of 28. Mean scores indicated that students’ rated all five dimensions of the educational environment in this institution as an average. The significant differences were found between overall mean score; mean score of teachers, academic self-perception & social self perception of students and different academic year. Conclusion: The overall mean DREEM scores indicate a more positive academic learning environment. Although the overall learning environments score of this institution observe as an average, none of the items represents ‘excellent’ score or real positive academic learning environment.